The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fenrg.2021.718310
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biowaste: A Multi-Objective Optimization Platform for Combined Heat, Power and Fuel

Abstract: Biomass, bioenergy and negative emission technologies are inherent to the future design of energy systems. Urban clusters have a growing demand for fuel, heat and electricity, which is both a challenge and an opportunity for biomass-based technologies. Their deployment should meet demand, while minimizing environmental impact and staying cost-competitive. We develop a systematic approach for the design, evaluation and ranking of biomass-to-X production strategies under uncertain market conditions. We assemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Mathematical programming and optimization methods have been applied intensively to similar superstructure optimization problems (Gassner and Maréchal, 2009;Tock et al, 2010;Santibañez-Aguilar et al, 2011;Viana Ensinas et al, 2013;Celebi et al, 2017;Castro-Amoedo et al, 2021). As noted by Liu et al (2012), when generating results by means of optimization, deriving a set of feasible alternatives may be preferred to the generation of a single system designone that is only potentially optimal under certain external conditions.…”
mentioning
confidence: 99%
“…Mathematical programming and optimization methods have been applied intensively to similar superstructure optimization problems (Gassner and Maréchal, 2009;Tock et al, 2010;Santibañez-Aguilar et al, 2011;Viana Ensinas et al, 2013;Celebi et al, 2017;Castro-Amoedo et al, 2021). As noted by Liu et al (2012), when generating results by means of optimization, deriving a set of feasible alternatives may be preferred to the generation of a single system designone that is only potentially optimal under certain external conditions.…”
mentioning
confidence: 99%
“…Economic and environmental models are integrated into a process integration (PI) model, adapted from Butun et al 50 and Castro-Amoedo et al 51 The objective is to minimize Total Annualized Cost (TC). The economic model links the PI stage with monetary flows and is used to compute the total cost of the system (eqn (2)), composed of investment (Capex) and operating expenses (Opex).…”
Section: Modeling and Optimizationmentioning
confidence: 99%
“…The rising need to create a decarbonized supply chain of energy critical metals motivates scientific advances in material-efficient pathways to harness earth abundant silicate resources. [1][2][3][4] The opportunity to fix anthropogenic CO 2 emissions via thermodynamically downhill carbon mineralization routes while co-recovering energy critical metals such as nickel and iron motivates scientific advances in accelerating these pathways. [1][2][3]5,6 Prior advances in this field were exclusively focused on carbon mineralization with limited attention being given to the co-recovery of energy critical metals that are present in earth abundant silicate resources such as serpentine (Mg 3 Si 2 O 5 (OH) 4 ) and olivine ((Mg,Fe) 2 SiO 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]5,6 Prior advances in this field were exclusively focused on carbon mineralization with limited attention being given to the co-recovery of energy critical metals that are present in earth abundant silicate resources such as serpentine (Mg 3 Si 2 O 5 (OH) 4 ) and olivine ((Mg,Fe) 2 SiO 4 ). [1][2][3][4]7 However, recent advances have shown that organic ligands such as ethylenediaminetetraacetic acid (EDTA) are effective in facilitating the co-recovery of energy critical metals such as nickel, while enabling accelerated carbon mineralization. However, scalable realization of these pathways remains limited by the lack of mechanistic insights into the complex chemomorphological interactions underlying the co-recovery of energy critical metals with inherent carbon mineralization.…”
Section: Introductionmentioning
confidence: 99%